Use of dried distillers grains with soluables (DDGS) for incremental replacement of soybean meal (SBM) in a Boer goat diet - Behrens, Anna A.; Crane, Alison R.; Lattimer, James M.; Jones, Cassandra K. (My University, 2018)
Dried distiller’s grains with solubles is a co-product of ethanol manufacturing. It is highly available in the Midwest and is relatively inexpensive compared to soybean meal. There is a 17% savings when purchasing DDGS instead of SBM. However, there is limited data describing how DDGS inclusion may impact goat growth performance. The objective of this experiment was to evaluate the impact of including DDGS at expense of SBM on Boer goat growth performance. The experiment was done over 47 days, with a 14-day step-up ration, beginning prior to the start of study. There were 48 goats on trial, 3 goats per pen (4 pens per treatment) and were housed at the Kansas State University Meat Goat Center. The 4 treatments being tested were, 1.) 0% SBM replaced by DDGS, 2.) 33% SBM replaced by DDGS, 3.) 66% SBM replaced by DDGS, and 4.) 100% SBM replaced by DDGS. All diets were pelleted and contained roughage to replace supplementation. Goats were fed daily, with feeder and goat weights recorded weekly to calculate BW, ADG, ADGI, and G:F, with P<0.05, being a significant difference. At the conclusion of the experiment, two goats from each pen were slaughtered at a USDA inspected facility with the following carcass data collected: HCW, carcass yield (%), loin eye area, and loin eye depth. Data was analyzed using the GLIMMIX procedure of SAS. There were no statistical differences (P>0.05) in goats fed various treatments on BW, ADG, or ADFI. There was a linear increase (P<0.05) in G:F with goats fed 66% and 100% DDGS having greater (P<0.05) G:F than those fed 0 or 33% DDGS. There were no differences (P>0.10) in carcass data regardless of DDGS inclusion. In summary, there was no detrimental effects caused by replacing SBM with DDGS at any level of replacement. It may be cost effective to replace SBM with DDGS.
Keywords: Spring 2018